Pemetaan Sebaran Karamba Jaring Apung Berdasarkan Zona Dan Tingkat Skala Usaha Menggunakan Drone Di Waduk Riam Kanan Provinsi Kalimantan Selatan - Muhammad Nur; Muhammad Ahsin Rifa'i; Rizmi Yunita; Leila Ariyani Sofia (EnviroScienteae, 2020)
Aquaculture is growing rapidly in Banjar District of Kalimantan Selatan Province, including on Riam Kanan Reservoir which is a center for floating net cage aquaculture. The increasing aquaculture on Riam Kanan Reservoir is not supported by adequate and actual data regarding the distribution, number of plots and number of fishery household (FHs) of floating net cage aquaculture. Complete, accurate and actual data is needed as one of the considerations in implementing sustainable aquaculture management policies. This study aims to map the distribution of floating net cages based on zones and business scale level, analyze the number of plots and the number of FHs of floating net cage aquaculture on Riam Kanan Reservoir. The study was conducted in July-October 2019 using 2 survey methods: a drone survey to collect aerial photographs and a field survey to identify the number of FHs and floating net cage plots based on business scale level. The results of aerial photography were analyzed using the Agisoft Metashape Professional and Arcgis 10.7 applications. Field survey data were analyzed using the Archgis 10.7 application and Microsoft Excel. The floating net cage is spread over 6 zones totaling 4,263 plots, consisting of criteria for small business scale 1,774 plots, medium scale 1,234 plots and large scale 1,255 plots. FHs of floating net cage aquaculture spread in 7 villages as many as 425 units with the criteria of 331 small scale business, 87 medium scale and 28 large scale. The plots and FHs of floating net cage aquaculture on Riam Kanan Reservoir has increased significantly over the past 4 years.